Familial Adenomatous Polyposis and Desmoid Tumor Treated with Multivisceral Transplantation and Kidney Autotransplantation: Case Report and Literature Review - Libor Janousek; Robert Novotny; Michal Kudla; Martin Oliverius; Petr Wohl; Joan Minguet; Jan Martinek; Tomas Hucl; Jiri Fronek (Case Reports in Surgery)
Introduction. Desmoid tumours (DT) are commonly associated with Gardener’s syndrome. Their surgical resection may be complicated by their close proximity to major vessels, multiple organ involvement, and frequent local recurrence. Multivisceral transplantation (MVTx) is an alternative treatment for patients with intestinal and liver failure. In patients with DT closely associated with renal structures but without end-stage kidney disease, concomitant excision of the patient’s own kidney, ex vivo tumour resection with nephron-sparing surgery, or autotransplantation has been proposed. Case Presentation. A 36-year-old Caucasian female weighing 60 kg with Gardener’s syndrome with a history of abdominal surgery was presented to our department with progressive abdominal distention associated with paroxysmal pain. With the use of CT, the patient was diagnosed with a mass arising from the mesenterial region. The patient had normal kidney function and nonalcoholic steatohepatitis. The patient was indicated for MVTx. Management and Outcome. After 16 months on the waiting list, the patient received a multivisceral graft from a deceased donor. Following the restoration of graft vascular flow, the patient’s right kidney was removed and the DT dissected ex vivo before autotransplantation into the right pelvic fossa. The patient received immunosuppressive, antithrombotic, and antibiotic treatment. There was no acute rejection, though the patient experienced pulmonary infection, dysphagia, and oesophageal reflux with fungal infection. The patient had required temporary dialysis for acute renal failure for 75 days. One year after the surgery, nausea and violent vomiting caused delayed gastric emptying caused by spastic pylorus. Clinical improvement was achieved using gastric peroral endoscopic myotomy (G-POEM). Conclusion. MVTx with kidney autotransplantation is a feasible treatment option in patients with familiar adenomatous polyposis complicated by an abdominal DT. Precise tumour dissection with nephron-sparing surgery was carried ex vivo. G-POEM was used to relieve MVTx-related gastroparesis. The patient had no disease reoccurrence after one-year follow-up.